Centralization and Oncologic Training Reduce Postoperative Morbidity and Failure-to-rescue Rates After Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy for Peritoneal Surface Malignancies: Study on a 10-year National French Practice. Issue 5 (November 2020) - Noiret, Barbara; Clement, Guillaume; Lenne, Xavier; Bruandet, Amelie; Glehen, Olivier; Voron, Thibault; Piessen, Guillaume; Eveno, Clarisse
Abstract : Objective: Evaluate at a national level the postoperative mortality (POM), major morbidity (MM) and failure-to-rescue (FTR) after cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) across time and according to hospital-volume. Background: CRS/HIPEC is an effective therapeutic strategy commonly used to treat peritoneal surface malignancies. However, this aggressive approach has the reputation to be associated with a high POM and MM. Methods: All patients treated with CRS/HIPEC between 2009 and 2018 in France were identified through a national medical database. Patients and perioperative outcomes were analyzed. A cut-off value of the annual CRS/HIPEC caseload affecting the 90-day POM was calculated using the Chi-squared Automatic Interaction Detector method. A multivariable logistic model was used to identify factors mediating 90-day POM. Results: A total of 7476 CRS/HIPEC were analyzed. Median age was 59 years with a mean Elixhauser comorbidity index of 3.1, both increasing over time ( P < 0.001). Ninety-day POM was 2.6%. MM occurred in 44.2% with a FTR rate of 5.1%. The threshold of CRS/HIPEC number per center per year above which the 90-day POM was significantly reduced was 45 (3.2% vs 1.9%, P = 0.01). High-volume centers had more extended surgery ( P < 0.001) with increased MM (55.8% vs 40.4%, P < 0.001) but lower FTR (3.1% vs 6.3%, P = 0.001). After multivariate analysis, independent factors associated with 90-day POM were: age >70 years ( P = 0.002), Elixhauser comorbidity index ≥8 ( P = 0.006), lower gastro-intestinal origin, ( P < 0.010), MM ( P < 0.001), and <45 procedures/yr ( P = 0.002). Conclusion: In France, CRS/HIPEC is a safe procedure with an acceptable 90-day POM that could even be improved through centralization in high-volume centers. Abstract : Supplemental Digital Content is available in the text